Peningkatan Kemampuan Menulis Permulaan Siswa Dengan Disabilitas Fisik (Cerebral Palsy) Melalui Media Pasir Kinetik - Lesriwanti Boang Manalu; Antoni Tsaputra; Damri Damri; Johandri Taufan (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to improve early writing skills of students with physical disabilities, specifically cerebral palsy, through the use of kinetic sand as a learning medium. The research was motivated by the low ability of students to write letters, numbers, and simple words independently and neatly due to limitations in fine motor control. This study employed a Classroom Action Research design conducted in two cycles in Grade III at SLB Negeri Salak. The research subjects consisted of two students, identified as AM and RB. The assessed aspects included the ability to write letters A–Z, numbers 1–10, and simple words independently and legibly. Data were collected through observation and performance tests and analyzed using descriptive quantitative methods based on percentage scores. The results showed a significant improvement in both subjects. In the initial condition, AM achieved 33.33% and RB 26.67%. In Cycle I, the scores increased to 60.0% for AM and 46.7% for RB. Further improvement was observed in Cycle II, with AM reaching 80.0% and RB 66.7%. These findings indicate that kinetic sand is effective in enhancing early writing skills of students with cerebral palsy, as it provides sensorimotor stimulation that supports hand coordination and fine motor control. Therefore, kinetic sand can serve as an adaptive and innovative instructional medium to develop early writing skills in students with physical disabilities.